Artificial Molecular Machines Powered by Light - Matteo Amelia; Monica Semeraro; Serena Silvi; Alberto Credi (CHIMIA, 2008)
The bottom-up construction and operation of mechanical machines of molecular size is a topic of great interest for nanoscience, and a fascinating challenge of nanotechnology. Like their macroscopic counterparts, nanoscale machines need energy to operate. Although most molecular motors of the biological world are fueled by chemical reactions, light is a very good choice to power artificial molecular machines because it can also be used to monitor the state of the machine, and allows systems to be obtained that show autonomous operation and do not generate waste products. By adopting an incrementally staged design strategy, photoinduced processes can be engineered within rotaxane-type structures with the purpose of obtaining light-powered molecular machines. In this short review we will illustrate such an approach by describing some systems investigated in our laboratories.